Generation 4.0 of the programmer selection decision support system: MCDM-AHP and ELECTRE-elimination recommendations - Erene Gernaria Sihombing; Ester Arisawati; Linda Sari Dewi; Rinawati Rinawati; Frisma Handayanna; Akmaludin Akmaludin (Institute of Advanced Engineering and Science, 2023)
The industrial world in the era of generation 4.0 needs personnel related to human resources who can handle crucial problems, especially in terms of data digitalization. The purpose of this paper is to analyze the supporting criteria that can be used as a measure of programmer selection for the needs of the industrial world which can provide optimal decisions and pay attention to the use of multi-criteria that have different quantitative assessments such as criteria related to contradictory times in its application. The problem, in the industrial world, does not only require speed alone but requires professional staff who can transform into digital technology, digitalization technology is needed in terms of the data conversion and transferring process, so a programmer has an important role in changing favorable conditions because it requires a selection process to get the best professional from several programmers. The method that can be used in multi-criteria decision-making-analytic hierarchy process (MCDM-AHP) and elimination et choix traduisant la realite (ELECTRE) methods in the concept of elimination. This method is part of the MCDM, which uses eight criteria in the selection and evaluation process. The results obtained from several selected programmers produce several professionally selected people, and can be used as an optimal benchmark for the programmer selection and evaluation process with a long preference index stage through the elimination process, this provides evidence that the selection and evaluation process can determine decision making which is optimal for a select number of programmers that only a few have through the aggregate dominant matrices.